Hubungan Daya Terima Makanan Dengan Status Gizi Anak Di Panti Asuhan Darunajah Semarang - Lilia Puspita Sari; Agus Sartono; Mufnaetty - (Universitas Muhammadiyah Semarang, 2015)
The food service is a series of activities starting from planning the menu, processing up to the evaluation in order to provide meals for groups of people (residents) in an institution. One ofthe institutions organizing the food is an orphanage. At the beginning of observation by the author at the Orphanage Darunajah Semarang, the authors look at the rest of the food was pretty much after the kids eat. This makes the authors to examine more interested in the quality of food that isheld in an orphanage.The Purpose of the research (study) was to know the children's acceptance of food thats provided by Darunajah Orphanage Semarang and Its relationship with the nutritional status of thechildren. This type of research is descriptive and analytical research in the field of nutrition with cross sectional approach. The number of sample thats used in the study, are 35 children who live at Darunajah Orphanage Semarang, have been taken with simple random sampling. Nutritional status was measured by Body Mass Index (BMI) and the food acceptance was measured with acounting leftovers. The relations of the food acceptance with nutritional status analyzed with Rank-Spearman correlation test. The results showed thats 48,6% children were 13-17 years old.The youngest is 6 years old and the oldest 22 years old. Female child more than the male child, are 19 children (54,3%) more than 16 children (45,7%). Almost all children whos live at theOrphanage (85,7%) could receive food properly. The range of Childrens to food acceptanceis 51,0% to 100%. Most of the children (91.4%) have a normal nutritional status, there are nochildren with malnutrition, espcially the category of bad nutritional status. There is a positive relationship between the level of childrens food acceptance with the nutritional status of children.Darunajah Orphanage Semarang was advised to make a cycle menu for children's meals so that food is more varied and have nutritional standards in order to meet the balanced nutritionalfoods. In this case Orphanage can ask for help from a nutritionist health center or Health Office of Semarang Municipality.Keywords: Orphanage, The Level of Food Acceptance, Nutritional Status.